Inspirations for design - Terrenghi, L.; Harper, Richard; Sellen, Abigail (Open Session, Ubicomp 2006, 2006)
We propose that diversity of human experience should be the focus for design in Ubicomp. This view is contrary to the model than underscores the bulk of Ubicomp research which tends to seek ways of computationally sup-porting and enabling the predictable, the determinate and the measurable. We contend that this approach runs the risk of producing user experiences which can be sterile and mechanical. In contrast, designing for diversity in Ubicomp can inspire people to be their own designers, and to express themselves in indi-vidual ways.